New Smart Antimicrobial Hydrogels, Nanomaterials, and Coatings: Earlier Action, More Specific, Better Dosing?. Issue 1 (12th October 2020) - Tallet, Lorène; Gribova, Varvara; Ploux, Lydie; Vrana, Nihal Engin; Lavalle, Philippe
Abstract: To fight against antibiotic‐resistant bacteria adhering and developing on medical devices, which is a growing problem worldwide, researchers are currently developing new "smart" materials and coatings. They consist in delivery of antimicrobial agents in an intelligent way, i.e., only when bacteria are present. This requires the use of new and sophisticated tools combining antimicrobial agents with lipids or polymers, synthetic and/or natural. In this review, three classes of innovative materials are described: hydrogels, nanomaterials, and thin films. Moreover, smart antibacterial materials can be classified into two groups depending on the origin of the stimulus used: those that respond to a nonbiological stimulus (light, temperature, electric and magnetic fields) and those that respond to a biological stimulus related to the presence of bacteria, such as changes in pH or bacterial enzyme secretion. The bacteria presence can induce a pH change that constitutes a first potential biological trigger allowing the system to become active. A second biological trigger signal consists in enzymes produced by bacteria themselves. A complete panel of recent studies will be given focusing on the design of such innovative smart materials that are sensitive to biological triggers. Abstract : Medical device‐associated infections, together with resistance to antibiotics, are growing problems worldwide. To reduce the development of resistance, new antibacterial systems that locally respond to bacterial infections are being increasingly studied. In this progress report, the most cutting‐edge approaches of smart antibacterial drug delivery systems are described.